The Route of Hydrothermal Synthesis Zeolite‑A from the Low‑Grade Perak kaolin, Malaysia - Norsuhailizah, Sazali; Zawati, Harun; Tijjani, Abdullahi; Noor Hasliza, Kamarudin; Norazlianie, Sazali; Mohd Riduan, Jamalludin; Siti Khadijah, Hubadillah; Siti Salwa, Alias (Springer, 2022)
Zeolite A was successfully synthesized using Perak kaolin which acts as the main source of silica and alumina. The process of beneficiation was conducted on raw kaolin to remove the impurities that existed in natural kaolin and also to increase the physical and chemical characteristic of kaolin. The kaolin was continued to be heated in the furnace with the temperature of 6000C for 4 h which described as a metakaolinization process that transformed it into the amorphous stage. The raw kaolin was characterized by XRD, FESEM, FTIR, PSA, TGA, while metakaolin by XRD, FESEM and FTIR. The mixture of zeolite A was achieved by adding the metakaolin into sodium hydroxide (NaOH) solution without adding other sources of silica and alumina. The solution mixture was stirred for 24 h before undergoing the process of hydrothermal synthesis. Two optimum conditions were studied for Zeolite A synthesizing, which were different molarity of sodium hydroxide and crystallizations time during the hydrothermal process. The successful synthesis of Zeolite A was then characterized by XRD, FESEM, FTIR, PSA, and BET surface area. The BET surface area of Zeolite-A is higher, 5.26 m2/g, compared to natural zeolite, 2.9 m2/g. As demonstrated in this work, Perak kaolin which was successfully synthesized into Zeolite-A with 2 M NaOH and 12-h crystallization time, gave a higher crystallinity percentage, 72.97%. The results obtained revealed that formation The of zeolite A has been highly affected by the NaOH molarity and crystallization time used in the combination of reactions.